Toward Competitive Advantage: Harnessing Artificial Intelligence for Business Innovation and Entrepreneurial Success - Muhammad Ade Kurnia Harahap; Abu Muna Almaududi Ausat; Muhammad Sani Kurniawan (Jurnal Minfo Polgan, 2024)
The digital revolution of the past few decades has significantly transformed the business paradigm. One of the technologies dominating this change is artificial intelligence (AI). AI has opened new opportunities in the business field with its ability to process data rapidly and detect previously unseen patterns. The aim of this research is to identify the potential utilization of AI in enhancing operational efficiency and business innovation. The research method employed is a literature review with a qualitative approach. Data used are sourced from Google Scholar for the period from 2017 to 2024. The findings of this research indicate that in an increasingly competitive and dynamic digital era, artificial intelligence (AI) has become a key driver for companies aiming to remain relevant and successful in a constantly changing environment. The use of AI opens new opportunities and stimulates business innovation by enabling companies to optimize strategies, enhance operational efficiency, and create more personalized customer experiences. However, the utilization of AI also brings challenges and risks, including data privacy and security concerns, as well as biases in AI decision-making. To address these challenges, companies must focus on talent development, collaboration among stakeholders, and cultural and organizational paradigm shifts.